Dehydrated potato flakes - Candado, Jovy A.; Carrillo, Jan-Michael Y.; Cuares, Reydell A.; Reyes, Katrina S.G (College of Engineering, 1998)
Product: Dehydrated potato flakes -- Plant capacity: 9200 kg of dehydrted potato flakes/day -- No. of operating days/year: 300 -- Plant location: Benguet -- Target market: snack food manufacturers, various food establishments (hotels, restaurants, fastfood chains) -- Total capital investment: Php 35,741,571.00 -- Payback period: 3.1 years -- Return on investment: 32.41% -- Break-even capacity/day: 2,425 kg -- Break-even selling price: Php 43.04/kg -- Proposed selling price: Php 55.00/kg